A paradox of the second order digital divide in higher education institutions of developing countries: case of Zimbabwe - Dube, Sibusisiwe (Department of Information Systems, 2021)
Although this is not a new research phenomenon, the literature has often associated the digital divide (second order or otherwise) with sociodemographic, sociocultural and socioeconomical factors as reasons for the digital divide. However, there is little presence in the literature into the underlying structures (physical or abstract arrangement) leading to the divide. This means that the underlying structures leading to this problem have so far been ignored and require scholarly attention. This study, therefore, identifies and explains the structures leading to the second order digital divide, a problem relating to the unequal use of information and communication technologies (ICTs) which is more prevalent in the higher education institutions (HEIs) of developing countries. Before the structures that lead to the second order digital divide could be explained the interlocking dynamics of ICT adoption needed to be identified. Structuration Theory was employed as a sensitising tool for collecting, analysing, and interpreting qualitative data for this interpretivist research. Novel qualitative data were collected from a purposive sample drawn from a single HEI of Zimbabwe, a developing country of high literacy. Directed content analysis generated insightful explanations of the structures leading to the second order digital divide at the HEI case. Preliminary analysis based on a deductive logic approach identified signification, domination, and legitimation as some of the structures leading to the second order digital divide at the HEI case. Further analysis based on an inductive logic approach revealed additional belief, institutional and governance structures which manifested from the interlocking dynamics of ICT adoption, involving resources, leadership, adoption behaviours and empowerment. These findings contributed to practice by explaining the underlying structures of the second order digital divide, for the benefit of ICT4D researchers, and by suggesting interventions to HEI policy-makers for reducing the second order digital divide. The results also make an iv explanatory contribution to theory by presenting a model of the interlocking dynamics of ICT adoption for theorising about the complex second order digital divide.